Pharmacodynamic Profiling of Bevacizumab in Combination with Paclitaxel for Advanced Cervical Cancer: A Network Pharmacology and Molecular Docking Approach - Melati Ganeza; Enricko Hotma Jonifar Siregar (The Indonesian Journal of General Medicine, 2025)
Introduction: Cervical cancer is a leading cause of cancer-related morbidity and mortality in women globally. The combination of Bevacizumab, an anti-VEGFA monoclonal antibody, with Paclitaxel-based chemotherapy has demonstrated significant clinical benefit in advanced stages, yet the underlying pharmacodynamic mechanisms of synergy are not fully understood. This study aims to elucidate these mechanisms using an integrated computational approach. Methods: A network pharmacology and molecular docking strategy was employed. Drug targets for Bevacizumab and Paclitaxel were sourced from DrugBank and PubChem, while cervical cancer-associated genes were obtained from GeneCards and DisGeNET. Shared targets were identified via intersection analysis. A Protein-Protein Interaction (PPI) network was constructed using STRING and analyzed with Cytoscape. Functional enrichment analysis (GO/KEGG) was performed using clusterProfiler and DAVID. Molecular docking simulations between Bevacizumab-VEGFA and Paclitaxel-β-tubulin were conducted using AutoDock Vina. Results: Intersection analysis yielded 168 overlapping targets. PPI network topology identified VEGFA, AKT1, TP53, EGFR, and MAPK1 as core hub proteins. Enrichment analysis revealed significant involvement in biological processes and pathways central to cervical cancer, including angiogenesis, apoptosis, PI3K-AKT, VEGF, mTOR, p53, and MAPK signaling (p < 0.01). Molecular docking confirmed strong binding affinities for Bevacizumab with VEGFA (-10.2 kcal/mol) and Paclitaxel with β-tubulin (-9.8 kcal/mol). Discussion: The findings suggest that the Bevacizumab-Paclitaxel combination exerts synergistic anti-tumor effects through multi-target, multi-pathway regulation. Bevacizumab inhibits angiogenesis and may promote vascular normalization, potentially enhancing Paclitaxel delivery. Paclitaxel induces mitotic arrest and apoptosis. Their concerted action on interconnected hubs and pathways (PI3K-AKT, VEGF, mTOR, p53, MAPK) provides a mechanistic rationale for the improved clinical outcomes observed in trials like GOG-240. Conclusion: This integrative computational study delineates a pharmacodynamic model for the synergy of Bevacizumab and Paclitaxel in advanced cervical cancer, involving complementary modulation of angiogenesis, proliferation, and apoptosis pathways. The results support the clinical use of this combination and highlight the utility of network pharmacology and molecular docking as predictive tools in oncology.